The Effect of A Number Sense Education Program Supported By Web 2.0 Tools on The Number Sense Development of First Grade Elementary School Students - Zuhal Akbabaoğlu; Özgün Uyanık Aktulun (e-Kafkas Eğitim Araştırmaları Dergisi)
This research was designed to evaluate the effectiveness of a Number Sense Education Program enhanced by Web 2.0 Tools on the development of number sense among first-grade elementary students. The study's cohort comprised 44 children, divided into an experimental group of 23 and a control group of 21. Employing a quasi-experimental design from quantitative research methodologies, data was collected using the "Number Sense Screener (NSS)"—originally developed by Jordan et al. (2012) and later adapted for Turkish first-grade students by Uyanık Aktulun (2019) alongside a "General Information Form" to collect personal data from families. Over the course of 12 weeks, the experimental group participated in the Web 2.0 Tools-supported Number Sense Education Program, conducted by the researcher, while the control group engaged in regular curriculum lessons. The findings revealed statistically significant improvements in the experimental group's pre-test and post-test scores across several NSS subdimensions, including Number Recognition, Number Comparisons, Nonverbal Calculation, Story Problems, and Number Combinations, as well as in their overall NSS scores (p<.05). However, no significant change was detected in the Counting Skills subdimension (p>.05). Furthermore, a statistically significant difference emerged between the experimental and control groups' post-test average scores in the NSS subdimensions and overall score (p<.05), underscoring the beneficial impact of Web 2.0 Tools-supported educational processes on enhancing number sense skills.